Dark local knowledge: the yet-to-be scientifically discovered and locally acknowledged aspects of local knowledge systems - Renata Sõukand (BMC, 2024)
Abstract This essay brings forward the idea that there is more than meets the eye in local knowledge systems than what science can show us now. To comprehend this, we need to make a conceptual jump and look for the "dark matter" (the notion borrowed from astronomy that refers to a hypothetical form of matter that does not interact with light or electromagnetic fields) that can potentially sustain local knowledge. Considering that it is a complex of knowledge, practices, and beliefs contained in TEK, knowledge in LEK does not correspond to the notion of knowledge in science. Therefore, in order to map LEK-science interactions, we will refer to the concept of peoples' knowledge of LEK as acknowledgement and the scientific recognition and awareness of information, facts, and principles as knowledge. Applying this to a Johari Window, we can observe four categories of LEK in a known-unknown/acknowledged-unacknowledged matrix. We can refer to unknown and unacknowledged as dark local knowledge. Indeed, local knowledge systems contain many aspects that modern science cannot yet explain, as a major part of its components are not even considered in scholarly research. Dark local knowledge can potentially provide us with the invaluable touch of experience of countless generations, opening different ways of seeing reality.